Eksplorasi Keanekaragaman Jenis Mangrove di Pulau Gantan, Tapak Kuda, Kabupaten Langkat - Febriyanti, Putri; Sudibyo, Mufti; Riyanto, Riyanto; Nasution, Jamilah (Universitas Medan Area, 2023)
The purpose of this research is to identify the types and characteristics of mangroves on Gantan Island and to evaluate the environmental conditions around the mangrove locations on the island. Mangrove samples were collected through exploration around Gantan Island by closely observing the various mangrove species, taking direct photographs of leaves, roots, flowers, and fruits, and then describing their characteristics. The research results indicate the presence of 11 plant species, including 6 true mangrove species such as Exoecaria agallocha, Xylocarpus granatum, Bruguiera gymnorhizza, Avicennia alba, Sonneratia caseolaris, and 3 associated mangrove species including Acanthus ilicifolius, Hibiscus tiliaceus, and Terminalia catappa. Additionally, non-mangrove plants like grasses and Casuarinaceae trees were also found. Some observation points, such as points 1 and 7 located directly along the open sea, experienced high sea erosion due to large waves, causing damage to the natural habitat. Local residents have undertaken reforestation efforts to restore the damaged habitat. Observation point 6 also experienced sea erosion as it is situated along a large river. Meanwhile, observation points 2, 3, 4, and 5 are still areas with pristine natural conditions in accordance with the mangrove perpendicular zone.